2019
DOI: 10.1002/phar.2197
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation and Nonadherence to Medications for Chronic Conditions after Hematopoietic Cell Transplantation: A 6‐Year Propensity Score–Matched Cohort Study

Abstract: Introduction Hematopoietic cell transplantation (HCT) is an established curative option for patients with hematological malignancies and other life‐threatening conditions. Evidence on nonpersistence and nonadherence to oral medications for chronic conditions among patients following HCT is lacking. Objectives This study aims to examine patterns of oral medication use for chronic conditions following HCT in the U.S. population. Methods Nonpersistence and nonadherence to oral medications for diabetes, hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Evidence has shown that medication nonadherence is associated with an increase in complications of chronic conditions and hospital visits ( Kaul et al, 2017 ). Also, medication nonadherence is associated with the progression of the disease for cancer survivors, which is likely to worsen the quality of life of patients ( Shafrin et al, 2017 ; Zhou et al, 2019 ). Given an increase in the amount of annual health care utilization and a worse quality of life, it is likely there would be an increase in the costs of patients ( Epstein et al, 2017 ; Sawaya et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that medication nonadherence is associated with an increase in complications of chronic conditions and hospital visits ( Kaul et al, 2017 ). Also, medication nonadherence is associated with the progression of the disease for cancer survivors, which is likely to worsen the quality of life of patients ( Shafrin et al, 2017 ; Zhou et al, 2019 ). Given an increase in the amount of annual health care utilization and a worse quality of life, it is likely there would be an increase in the costs of patients ( Epstein et al, 2017 ; Sawaya et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…But during the transition from childhood to adulthood the rate of NA can reach a peak of 40 to 70% [21,22,24‐27]. Few data exist for allo‐HCT recipients; nevertheless, authors have described a similar rate of non‐adherence ranging from 20% to 60% in adult and pediatric cohorts [1,28–32].…”
Section: Introductionmentioning
confidence: 99%
“…Nonadherence refers to when a patient does not follow a healthcare provider's instructions for taking a certain medication [1][2][3]5]. This includes taking too little or too much of the medication, stopping the medication without the consultation of a healthcare provider (referred to as non-persistence), or not starting the treatment at all.…”
Section: Medication Nonadherence and Discontinuation Backgroundmentioning
confidence: 99%
“…Nonadherence and discontinuation of medication is a particular challenge for the treatment of chronic diseases [4][5][6][7]. There are higher degrees of adherence for a treatment that cures an illness (77% adherence) when compared to a treatment that prevents an illness (63% adherence), and long treatments prompt a reduction in adherence to about 50% [10].…”
Section: Medication Nonadherence and Discontinuation Backgroundmentioning
confidence: 99%